Security Design - BOOT, ARNOUD W. A.; THAKOR, ANJAN V. (Journal of Finance, 1993)
ABSTRACT We explain why an issuer may wish to raise external capital by selling multiple financial claims that partition its total asset cash flows, rather than a single claim. We show that, in an asymmetric information environment, the issuer's expected revenue is enhanced by such cash flow partitioning because it makes informed trade more profitable. This approach seems capable of shedding light on corporate incentives to issue debt and equity, as well as on financial intermediaries' incentives to issue multiple classes of claims against portfolios of securitized assets.